Makna Pesan Tersembunyi Dalam Film “Siksa Kubur” (Analisis Semiotika Roland Barthes) - Wahyudin, Affan; Hardian, Arvin; Ekowati, Sari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
‘Grave Torture’ movie tells the dramatic journey of a girl named Sita and her younger brother named Adil, whose lives changed completely after losing their parents due to terrorism. The story has many messages that are close to social and community issues in Indonesia. The purpose of this study is to find out the hidden meaning of the ‘Grave Torture’ movie based on Roland Barthes’ Semiotic Analysis. This research is a qualitative study with Roland Barthes’ semiotic analysis method which consists of three elements, denotation, connotation and myth. This data was obtained through the ‘Grave Torture’ movie. Through a reflective approach, this film reflects various forms of social messages that occur in society, especially those who are Muslim. Films become a medium of education and reflection on the dangers of trauma that damage the victims. This film reminds the audience to always be careful, create a positive environment and dare to fight negative thoughts and always dare to fight violence or other detrimental actions and provide support for victims.